Do we need to measure total serum IgA to exclude IgA deficiency in coeliac disease?. Issue 7 (17th February 2006) - Sinclair, D; Saas, M; Turk, A; Goble, M; Kerr, D
Abstract : Background: Screening for IgA deficiency in patients with coeliac disease is essential because of the increased incidence of IgA deficiency associated with the disease, which usually relies on the estimation of IgA levels in each case. Aim: To devise a method of excluding IgA deficiency without measuring total serum IgA in each case. Materials and methods: The optical density readings on enzyme-linked immunosorbent assay (ELISA) of 608 routine samples received for tissue transglutaminase (TTG) antibody testing for coeliac disease were compared with their total IgA concentrations. Dilution experiments were also carried out to ensure linear relationships between optical density on ELISA and IgA concentrations and to compare the sensitivities for TTG and endomysium antibodies in TTG-positive samples. Results and discussion: A clear relationship was shown between total IgA concentration and TTG optical density readings by ELISA. To ensure a positive TTG result if antibodies are present, it was possible to recommend an optical density level above which all samples have sufficient IgA. Samples with optical density <0.05 should be investigated further by estimating total IgA and, if low, samples should be subjected to immunofluorescence microscopy testing for IgA and IgG endomysium antibodies. Conclusions: An easier, more cost-effective and practical way of excluding IgA deficiency in the investigation on coeliac disease is reported.